2020
DOI: 10.1097/htr.0000000000000555
|View full text |Cite
|
Sign up to set email alerts
|

From Early Childhood to Adolescence: Lessons About Traumatic Brain Injury From the Ohio Head Injury Outcomes Study

Abstract: Objective: The Ohio Head Injury Outcomes study was a 12-year longitudinal study of early childhood traumatic brain injury (TBI). This article reviewed the findings pertaining to caregiver and family functioning and child cognition, behavior, social competence, emotional functioning, and academics. We further considered individual and social-environmental influences on recovery and interventions. Setting: Recruitment was completed at 3 children's hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Poorer pre-injury adjustment is a risk factor for poorer post-injury adjustment across the spectrum of TBI severity ( 5 , 28 ). Pre-injury family and environmental factors also significantly influence child behavioral outcomes, such that lower income, lower social and community connectivity, greater family dysfunction, and parental psychiatric symptoms act as vulnerability factors contributing to worse post-injury problems ( 5 , 19 , 29 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Poorer pre-injury adjustment is a risk factor for poorer post-injury adjustment across the spectrum of TBI severity ( 5 , 28 ). Pre-injury family and environmental factors also significantly influence child behavioral outcomes, such that lower income, lower social and community connectivity, greater family dysfunction, and parental psychiatric symptoms act as vulnerability factors contributing to worse post-injury problems ( 5 , 19 , 29 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The largest study of complex mild TBI published in 2011 showed that patients with mild TBI and intracranial hemorrhage had a substantial reduction in quality of life, participation in activities with others, and communication and care for themselves at 3 months after injury. 7 Since recovery after mild TBI is variable, with many children having residual long-term needs, 10 and since children with complex mild TBI may have more significant TBI, there is an unmet need to understand outcomes of children specifically with complex mild TBI.…”
mentioning
confidence: 99%
“…Consistent with prior research, lowest recorded Glasgow Coma Scale (GCS) scores and imaging findings were used to define TBI severity with GCS scores of 13-15 with associated CT and/or MRI findings identified as complicated mild, GCS scores of 9-12 as moderate TBI, and GCS scores of 3-8 as severe TBI. Consistent with prior research, the complicated mild and moderate groups were combined (Petranovich et al, 2020) and will be referred to as the moderate group hereafter.…”
Section: Participantsmentioning
confidence: 99%